The effect of rapid heat treatment on the high-temperature tensile behavior of superplastic Ti-6Al-4V - S. Rhaipu (2018)
The effect of rapid heat treatment on the microstructure and elevated-temperature tensile behavior of a Ti-6Al-4V sheet has been studied. Nonequiaxed secondary α phase, introduced by rapid heat treatment, increased the flow stress and changed the stress-strain behavior. A finer scale of the microstructures produced by rapid heat treatment, however, resulted in a stress-strain behavior that differed from that reported in the microstructures obtained from a slower, furnace heat treatment. These fine structures exhibited higher values of m, greater elongation, and lower flow stresses. The stress-strain behavior was found to be dependent on the prior-β grain size; this effect was not observed when the material was furnace heat treated in the β-phase field. The stress-strain curve gradually changed from exhibiting continuous strain hardening to exhibiting a peak stress followed by strain softening, i.e., the superplastic behavior of the as received material gradually diminished as the prior-heat-treatment temperature increased.